Neural networks applications for environmental safety assessment of roads in Ukraine - Naumov, Vitalii; Vnukova, Natalia; Zhelnovach, Ganna (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The analysis of problems and of approaches for ensuring the environmental safety of roads in Ukraine has been performed. The proposed mathematical model on the basis of neural networks allows numerical evaluation of quality of road area in the conditions of incomplete and fuzzy information. The proposed approach allows the determination of roads’ environmental safety level, the indication of necessity for arrangement of environmental monitoring stations, and allows the development of a number of activities for environmental protection on the road sections as well.